An analysis of taxpayer compliance using a cost-benefit approach. - Sor Tin, Saw (2019)
This study seeks to analyze and enhance understanding of taxpayer compliance with tax obligations in a systematic way by using the cost benefit approach. Data from a sample of 250 audited service tax payers are used to examine the compliance factors. The hypotheses are tested using Spearman’s rho for ordinal variables and biserial correlation for dichotomous data. A decision matrix is used to make a logical conclusion on the business firm reporting behavior based on the derived expected utility value and compliance level. The results show a positive significant correlation between taxable sales, return submission and taxpayer compliance, but taxpayer compliance has a negative relationship with deficiency amount, penalty, and three other variables. The study suggests that minor penalties are unlikely to deter non-compliant behavior and economic factors seem to exert more influence on compliance. The methodology and matrix diagram can be customized to the requirements of tax audit management for assisting in audit case selection and strategy program to detect underdeclaration and minimize shortfall in tax revenue. The taxpayer compliance-Correlation-Expected utility matrix analyzes the taxpayer’s expected utility function and compliance behavior, and provides an insight to what the most likely decision of a taxpayer is under certain assumptions.